Chronicle – Seminars - JORASZ, U.; SANKIEWICZ, M. (Archives of Acoustics, 1992)
The Chronicle contains information about:– The 38th Open Seminar on Acoustics OSA’91 September 17th—20th1991.– 4th Symposium on Sound Egineering and Mastering Gdańsk, 17-19 June, 1991.– The Polish Section of the Audio Engineering Society. Organizatory Meeting in Gdańsk – 18. 6. 1991. – 92nd AES CONVENTION - 24-27. 03. 1992 - VIENNA. Polish AES Section Report – NOISE-93